Ответы и объяснения

2012-03-15T15:56:57+00:00

а) 44/(-2,5)-6*(4,3*0,8-3,7) = -17,6-6 х (-0,26)= -16,04

б) (-11,2/(-2,8)-3,6+2,4)/(-0,4) = (4-3,6+2,4) : (-0,4) = 2,8/ -(0,4)= -7

в) -3,6*(-0,5)-(-3,2+0,8)*1,05 = 1,8-(-2,4)х1,05= 4,32

Лучший Ответ!
2012-03-15T16:03:04+00:00

а) 1) (4,3*0,8-3,7)=3,44-3,7=-0,26

2)44/(-2,5)=-17,6

3)6*(-0,26)=-1,56

4)-17,6-(-1,56)=-17,6+1,56=-16,04

б) 1)-11,2/(-2,8)=4

2) 4-3,6+2,4=2,8

3)2,8/(-0,4)=-7

в) 1)-3,6*(-0,5)=1,8

2)-3,2+0,8=-2,4

3)-2,4*1,05=-2,52

4)1,8-(-2,52)=1,8+2,52=4,32